Teaching NeuroImage: Neurovascular Consequences of Autonomic Dysreflexia. (25th January 2022) - Lineback, Christina M.; Moffet, Eric W.; Kim, Minjee
Abstract : An 18-year-old man with C6 quadriparesis presented with two 30-minute episodes of thunderclap headache, vision loss, new urinary incontinence, hypertension (200s/90s), and bradycardia more than 24 hours. Imaging demonstrated multifocal cerebrovascular narrowing (Figure 1), restricted diffusion, and hyperintense T2/FLAIR signal (Figure 2); transcranial Dopplers (TCDs) displayed increased velocities. Reversible cerebral vasoconstriction syndrome (RCVS) was diagnosed.